Green Synthesis of Copper Nanoparticles Using Withania somnifera and Its Antioxidant and Antibacterial Activity. (25th July 2022) - Shanmugapriya, J.; Reshma, C. A.; Srinidhi, V.; Harithpriya, K.; Ramkumar, K. M.; Umpathy, Dhamodharan; Gunasekaran, Krishnamoorthy; Subashini, R.
Abstract : This study employed green chemistry to synthesize copper nanoparticles (CuNPs) using fresh root extract of Withania somnifera . The size, shape, morphology, and stability of resultant CuNPs were investigated by UV-Vis spectroscopy, FTIR, transmission electron microscopy (TEM), and energy-dispersive spectrophotometer. Crude extracts were assessed phytochemically to determine the presence of alkaloids, flavonoids, phenols, saponins, steroids, and tannins. The UV-Vis absorption spectra show maximum absorption at 330 nm, and FTIR showed the presence of biological molecules responsible for reducing Cu + ions. In TEM and EDS analyses, the average diameter of the synthesized NPs was found to be 6.28 ± 1.13 nm . The crystal structure of synthesized nanoparticle was determined using XRD analysis and showed its peak at 36.34°, 43.33°, 50.47°, and 73.57°, which corresponds to the cubic lattice of copper. The synthesized nanoparticles (NPs) were tested for their in vitro antimicrobial activity against bacterial strains E. coli and S. aureus by the agar well diffusion method which showed higher efficiency against S. aureus . The antioxidant activity of the synthesized NPs was evaluated by DPPH assay, and the percentage of inhibition was found to be 62% at the concentration of 400 μ g/ml and the IC50 value was 51.53 μ g/ml. The present investigation suggests that the biosynthesized CuNPs showed prominent antibacterial and free radical scavenging potential. The result proved that root extract of W. somnifera could be applied for synthesis of nanoparticle CuNPs with high uniform particle size along with potent biological activity.